Visualization of single crosslinks and heterogeneity in polymer networks. (December 2022) - Tang, Zhongqiu; Jiang, Lingxiang
Abstract: At the very heart of any polymer networks are the crosslinks that interconnect neighboring chains and lock them in position to resist stress. The crosslinks and their spatial heterogeneity are expected to dictate network architecture, origin of elasticity, and transmission from macroscopic forces to local responses. Yet, direct confirmations of these predictions have been elusive largely because the traditional experimental means are limited to ensemble-averaged or reciprocal-space information. In this perspective, we call attention to the very recent developments that managed to visualize the crosslinks on a single-molecule level, which further localized their static, equilibrium positions in space and tracked their fluctuations around the equilibrium positions in time. Hopefully, these real-space information with unprecedent details can allow us to fully understand networks of complexity and to correlate macroscopic properties to nanoscopic structures. Graphic abstract: Image, graphical abstract At the very heart of any polymer networks are the crosslinks that interconnect neighboring chains and lock them in position to resist stress. The crosslinks and their spatial heterogeneity are expected to dictate network architecture, origin of elasticity, and transmission from macroscopic forces to local responses. Yet, direct confirmations of these predictions have been elusive largely because the traditional experimental means are limited to ensemble-averaged or reciprocal-space information. In this perspective, we call attention to the very recent developments that managed to visualize the crosslinks on a single-molecule level, which further localized their static, equilibrium positions in space and tracked their fluctuations around the equilibrium positions in time. Hopefully, these real-space information with unprecedent details can allow us to fully understand networks of complexity and to correlate macroscopic properties to nanoscopic structures.